2016
DOI: 10.1002/elsc.201500125
|View full text |Cite
|
Sign up to set email alerts
|

Rhodosporidium toruloides cultivated in NaCl‐enriched glucose‐based media: Adaptation dynamics and lipid production

Abstract: In the present report and for the first time in the international literature, the impact of the addition of NaCl upon growth and lipid production on the oleaginous yeast Rhodosporidium toruloides was studied. Moreover, equally for first time, lipid production by R. toruloides was performed under nonaseptic conditions. Therefore, the potentiality of R. toruloides DSM 4444 to produce lipid in media containing several initial concentrations of NaCl with glucose employed as carbon source was studied. Preliminary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 70 publications
(107 reference statements)
8
29
0
Order By: Relevance
“…The high lipid yields that ranged from 201.4 mg/g to 224.4 mg/g suggested that carbon sources in the hydrolysates were mainly channeled into lipid biosynthesis. These data were comparable to those obtained by Yarrowia lipolytica and Rhodosporidium toruloides on glucose (Qiao et al 2015;Tchakouteu et al 2017). Overall, the authors' results indicated that waste paper hydrolysates could serve as appealing substrates for lipid production.…”
Section: Compositional Analysis and Enzymatic Hydrolysis Of Waste Papersupporting
confidence: 80%
“…The high lipid yields that ranged from 201.4 mg/g to 224.4 mg/g suggested that carbon sources in the hydrolysates were mainly channeled into lipid biosynthesis. These data were comparable to those obtained by Yarrowia lipolytica and Rhodosporidium toruloides on glucose (Qiao et al 2015;Tchakouteu et al 2017). Overall, the authors' results indicated that waste paper hydrolysates could serve as appealing substrates for lipid production.…”
Section: Compositional Analysis and Enzymatic Hydrolysis Of Waste Papersupporting
confidence: 80%
“…a,b (data from Tchakouteu et al . ). It can be easily become understandable that onset of lipid accumulation was given only after remarkable exhaustion of the assimilable nitrogen found into the culture medium and, thereafter, large quantities of microbial lipids (in both absolute; g l −1 , and relative; % in DCW, values) were accumulated inside the yeast cells.…”
Section: Physiology Of Lipid Accumulation Processmentioning
confidence: 97%
“…T. elegans 14Á9 3 4 Á5 Flasks Zikou et al (2013) interesting alternative to the use of plant oils for biodiesel production because oleaginous yeasts, due to their unicellular morphology can be cultivated more easily than the fungi in large-scale bioreactors, whereas strains of these yeasts can transform a variety of substrates including low-or even zero-cost materials to SCO, which can then be transformed to biodiesel (Xue et al 2006;Li et al 2007;Zhao et al 2008;Li et al 2010;Xu et al 2012Xu et al , 2013Xu et al , 2016Xu et al , 2017Tsakona et al 2014Tsakona et al , 2016Karamerou et al 2015;Louhasakul and Cheirsilp, 2013;Tchakouteu et al 2015aTchakouteu et al , 2017Karamerou et al 2017). It is evident that as far as the synthesis of SCO that is aimed to be transformed in second-generation biodiesel is concerned, only hydrophilic carbon sources (i.e.…”
Section: Oleaginous Micro-organismsmentioning
confidence: 99%
See 2 more Smart Citations